Suddenly! - McNaughton, Colin (San Diego : Harcourt Brace, 1995)
Time after time, Preston the pig unknowingly outwits a hungry wolf that is trying to catch and eat him.
"First published in Great Britain in 1994 by Andersen Press"--T.p. verso.
470
Accelerated Reader AR
Keywords: Humorous stories; Pigs -- Fiction; Wolves -- Fiction